Uma proposta de escalonador baseado na disciplina Priority Queuing (PQ) para redes IEEE 802.16 - Ferreira, Flávio Alves (2011)
The IEEE 802.16 standard, also known as WiMAX (Worldwide Interoperability for Microwave Access), defines a broadband wireless access network (BWA) with metropolitan coverage, capable of achieving high data rates transmission, with easy deployment and maintenance. Its main advantage is the presence of an inherent QoS (Quality of Service) architecture. Two layers are specified, the Medium Access Control (MAC) layer and Physical Layer (PHY) [1] [2]. The MAC layer is connection-oriented. The heterogeneous traffic, nRT (non Real Time) and RT (Real Time), which is generated by network applications is managed as service flows. Each flow is defined by a direction, downlink (DL) or uplink (UL), and a set of parameters to standardize operations among stations. The flows are mapped into classes of service for QoS provisioning, according to your requirements. The main QoS mechanism is the scheduler, which is responsible for defining the order delivery of packets stored in the queues of the stations, but the standard does not define its policy of operation. As the bandwidth in WiMAX networks is a limited resource, and the traffic classes, RT and nRT, has different requirements such as the maximum latency, the purpose of this work is an extension of the scheduling mechanism for UL traffic presented in [3], based on Priority Queuing (PQ), to provide differentiated treatment with traffic prioritization. Aiming to increase the protection and isolation between traffic classes, RT and nRT, was created a new queue separating the requests of these classes. Aiming to increase the efficiency of resource utilization has been proposed a new scheme that pre-allocates the remaining resources in the UL, before receiving the bandwidth request, ie, in advance, straightly to the data transmission of the user stations. The assessment of this proposal was made by means of modeling and simulation, and the results showed that its performance was superior to the proposal presented in [3], reducing the average delay of rtPS (Real Time Polling Service) class and increasing the average throughput and resource utilization of nRT classes.